Nanocrystalline Fe-Fe2O3 particle-deposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2015)
The size-controlled growth of nanocrystalline Fe-Fe2O3 particles (2-3 nm) and their concomitant dispersion on N-doped graphene (Fe-Fe2O3/NGr) could be attained when the mutually assisted redox reaction between NGr and Fe3+ ions could be controlled within the aqueous droplets of a water-in-oil emulsion. The synergistic interaction existing between Fe-Fe2O3 and NGr helped the system to narrow down the overpotential for the oxygen reduction reaction (ORR) by bringing a significant positive shift to the reduction onset potential, which is just 15 mV higher than its Pt-counterpart. In addition, the half-wave potential (E-1/2) of Fe-Fe2O3/NGr is found to be improved by a considerable amount of 135 mV in comparison to the system formed by dispersing Fe-Fe2O3 nanoparticles on reduced graphene oxide (Fe-Fe2O3/RGO), which indicates the presence of a higher number of active sites in Fe-Fe2O3/NGr. Despite this, the ORR kinetics of Fe-Fe2O3/NGr are found to be shifted significantly to the preferred 4-electron-transfer pathway compared to NGr and Fe-Fe2O3/RGO. Consequently, the H2O2% was found to be reduced by 78.3% for Fe-Fe2O3/NGr (13.0%) in comparison to Fe-Fe2O3/RGO (51.2%) and NGr (41.0%) at -0.30 V (vs. Hg/HgO). This difference in the yield of H2O2 formed between the systems along with the improvements observed in terms of the oxygen reduction onset and E-1/2 in the case of Fe-Fe2O3/NGr reveals the activity modulation achieved for the latter is due to the coexistence of factors such as the presence of the mixed valancies of iron nanoparticles, small size and homogeneous distribution of Fe-Fe2O3 nanoparticles and the electronic modifications induced by the doped nitrogen in NGr. A controlled interplay of these factors looks like worked favorably in the case of Fe-Fe2O3/NGr. As a realistic system level validation, Fe-Fe2O3/NGr was employed as the cathode electrode of a single cell in a solid alkaline electrolyte membrane fuel cell (AEMFC). The system could display an open circuit voltage (OCV) of 0.73 V and maximum power and current densities of 54.40 mW cm(-2) and 200 mA cm(-2), respectively, which are comparable to the performance characteristics of a similar system derived by using 40 wt% Pt/C as the cathode electrode.

Nanocrystalline Fe-Fe2O3 particledeposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2017)

NiZn double hydroxide nanosheet-anchored nitrogen-doped graphene enriched with the gamma-NiOOH phase as an activity modulated water oxidation electrocatalyst - Nadeema, Ayasha; Dhavale, Vishal M.; Kurungot, Sreekumar (Nanoscale, 2017)
Herein, we report a facile solvothermal process to synthesize an active electrocatalyst for the oxygen evolution reaction (OER) in an alkaline medium by anchoring nanosheets of a NiZn double hydroxide over nitrogen doped reduced graphene oxide after enriching the system with the γ-NiOOH phase. This catalyst possesses a thin, porous and open layered structure, which makes the system more efficient and accessible for a better electrochemical water oxidation reaction. Moreover, we experimentally demonstrated that incorporation of Zn via a single-step solvothermal method provides an easy approach to obtain plenty of exposed γ-NiOOH phases to make the system more viable for OER with a small overpotential of 290 mV at 10 mA cm−2 and a Tafel slope of 44 mV per decade. In addition to this, the oxophilic nature of Zn in the (Zn)Ni-LDH/N-rGO catalyst helps to improve the long-term stability of the whole system. The obtained results open up possibilities for the design of future robust OER electrocatalysts by the use of very cheap and abundant materials like Ni and Zn in place of expensive Ir and Ru in the present commercial electrocatalysts.
Keywords: catalysis; Efficient Electrocatalyst; kinetics; Metal; Nickel-Hydroxide; oxide; Oxygen Evolution Reaction; performance; XPS Spectra; zinc

Glycine-induced electrodeposition of nanostructured cobalt hydroxide: a bifunctional catalyst for overall water splitting - Shilpa, Nagaraju; Nadeema, Ayasha; Kurungot, Sreekumar (ChemSusChem, 2019)
Herein, an interconnected alpha-Co(OH)(2) structure with a network-like architecture was used as a bifunctional electrocatalyst for the overall water splitting reaction in alkaline medium. The complexing ability of glycine with a transition metal was exploited to form [Co(gly)(3)](-) dispersion at pH 10, which was used for the electrodeposition. High-resolution TEM, UV/Vis-diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy were used to confirm that the as-synthesized materials had an alpha-Co(OH)(2) phase. The electrocatalytic oxygen and hydrogen evolution activity of the glycine-coordinated alpha-Co(OH)(2) was found to be approximately 320 and 145 mV, respectively, at 10 mA cm(-2). The material required approximately 1.60 V (vs. reversible hydrogen electrode; RHE) to achieve the benchmark of 10 mA cm(-2) for overall water splitting with a mass activity of approximately 63.7 A g(-1) at 1.60 V (vs. RHE). The chronoamperometric response was measured to evidence the stability of the material for overall water splitting for up to 24 h. Characterization of the catalyst after the oxygen and hydrogen evolution reactions was performed by XPS and showed the presence of a Co-II/Co-III oxidation state.
Keywords: cobalt; Electrochemistry; heterogeneous catalysis; Hydrogen; water splitting

[MoS4](2-)-Intercalated NiCo-layered double hydroxide nanospikes: an efficiently synergized material for urine to direct H-2 generation - Nadeema, Ayasha; Kashyap, Varchaswal; Gururaj, Rakshitha; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2019)
Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental 6 protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2- in its interlayer space. The [MoS4]' insertion as well as its effect on the electronic structure tuning is thoroughly studied via X-ray photoelectron spectroscopy in combination with electrochemical analysis. This insertion induces overall electronic structure tuning of the hydroxide layer in such a way that the designed catalyst exhibited favorable kinetics toward all the required reactions of hydrogen generation. This is why our homemade catalyst, when utilized both as a cathode and anode to fabricate a urea electrolyzer, required a mere X1.37 V cell potential to generate sufficient H2 by reaching the benchmark 10 mA cm-2 in 1 M KOH/0.33 M urea along with long-lasting catalytic efficiency. Other indispensable reason of selecting [MoS4]2- is its high-valent nature making the catalyst highly selective and insensitive to common catalyst-poisoning toxins of urine. This is experimentally supported by performing the real urine electrolysis, where the nanospike-covered Ni foam-based catalyst showed a performance similar to that of synthetic urea, offering its industrial value. Other intuition of selecting [MoS4]2- was to provide a ligand-based mechanism for hydrogen evolution half-cell [hydrogen evolution reaction (HER)] to preclude the HER-competing oxygen reduction. Another crucial point of our work is its potential to avoid the mixing of two explosive product gases, that is, H2 and O-2.
Keywords: hydrogen evolution reaction; Layered double hydroxide; nickel oxyhydroxide; sewage denitrification; urea oxidation reaction; urine/urea electrolysis

Co@CoAl-layered double hydroxide/nitrogen-doped graphene composite catalyst for Al-H2O-based batteries: simultaneous hydrogen production and electricity generation - Nadeema, Ayasha; Pandurang Kharabe, Geeta; Prakash Biswal, Dibya; Kurungot, Sreekumar (ChemElectroChem, 2020)
Currently, the low energy efficiency of water electrolysis has compelled research toward the development of novel and energy-effective strategies for low-cost H-2 generation. In this context, we report a new concept of simultaneous H-2 and electricity generation by separating out the exothermic self-sustained Al-H2O reaction via electrochemistry. In addition, to catalyze the cathodic water reduction reaction, a single-pot and environmentally benign synthesis method is adopted. It results in the design of an electrocatalyst composed of Co@CoAl-layered double hydroxide core-shell nanospheres anchored over in situ generated N-doped graphene. Toward the water reduction reaction, the designed catalyst shows a negative voltage shift of mere around 113 mV with respect to the commercial Pt/C catalyst to reach the benchmark 10 mA cm(-2), with excellent stability of approximately 86 % voltage retention after 12 h of continuous operation. The catalytic superiority of our material is evident when taken for battery-level testing; the fabricated device was able to deliver an average output voltage of around 0.95 V at a discharge current density of 5 mA cm(-2) along with H-2 liberation, which was also detected and quantified through gas chromatography.
Keywords: Al-H2O fuel cells; chronopotentiometry; core-shell structures; hydrogen evolution reaction; layered double hydroxides

Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.